2017
DOI: 10.1177/0973801017703513
|View full text |Cite
|
Sign up to set email alerts
|

Post-communist Transition as a Path Break: Comparing Legal Institutional Effects on Economic Growth between Path-breaking and Path-drifting Institutional Reforms

Abstract: This article explains the peculiarities of institutional effects on growth rates in postcommunist countries. By proposing a certain dependence of the institution-growth nexus on the mode of institutional grafting, the distinction between drift-phase and path-breaking institutional change is introduced. Theoretical juxtapositions show that transition countries' institutions built through path-breaking institutional reforms differ from those that emerge evolutionarily in the drift phase in a twofold manner in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Complementing path-dependency in understanding institutional uncertainty and change is the concept of path-break that, in contrast, suggests a move away from legacy institutions and re-orientation towards new institutional arrangements, economic principles and associated systems of norms and values (Williams and Vorley, 2017). This concept is particularly useful in understanding contexts that experienced radical forms of change, particularly the post-Socialist states where the new liberal market-based institutions are being implanted through path-breaking reforms to replace the old socialist-era institutional framework (Tamilina and Tamilina, 2017). At the firm level, path-break suggests that economic actors and their practices will gradually align with and reflect the key features embodied in the logic of market institutions (Williams and Vorley, 2017).…”
Section: Hrm In Smes Through the Lens Of Informal Institutions And Pa...mentioning
confidence: 99%
“…Complementing path-dependency in understanding institutional uncertainty and change is the concept of path-break that, in contrast, suggests a move away from legacy institutions and re-orientation towards new institutional arrangements, economic principles and associated systems of norms and values (Williams and Vorley, 2017). This concept is particularly useful in understanding contexts that experienced radical forms of change, particularly the post-Socialist states where the new liberal market-based institutions are being implanted through path-breaking reforms to replace the old socialist-era institutional framework (Tamilina and Tamilina, 2017). At the firm level, path-break suggests that economic actors and their practices will gradually align with and reflect the key features embodied in the logic of market institutions (Williams and Vorley, 2017).…”
Section: Hrm In Smes Through the Lens Of Informal Institutions And Pa...mentioning
confidence: 99%
“…The study also showed that investment stimulated economic growth. Tamilina and Tamilina (2014) explained the uniqueness of economic institutional effects on economic growth in postcommunist countries. Their study showed that the collapse of communism in the communist countries led to radical changes in political, social and economic systems of the former communist countries.…”
Section: Empirical Studies On Institutionalism and Economic Developmentmentioning
confidence: 99%
“…Tamilina and Tamilina 6 noticed that studies originating in post-communist countries negate the claim that free-market formal institutions per se may lead to economic prosperity in the course of transition. 7 They found that capitalist formal institutions are incompatible with post-communist informal norms because of the countries' historical experience with democracy and free markets.…”
Section: Introductionmentioning
confidence: 99%